Peningkatan Aktivitas Belajar dan Hasil Belajar Biologi Siswa melalui Strategi Pembelajaran Everyone Is a Teacher Here pada Kelas X SMA Negeri 3 Sengkang - Amir, Suharyanti; Ali, Alimuddin; Azis, Andi Asmawati (Universitas Negeri Makassar, 2018)
Abstract.Â This research is a classroom action research. The purpose of this study improves the activity and student learning outcomes through application of learning strategy Everyone is a Teacher Here. Research subjects are students of class X.I SMA Negeri 3 Sengkang. This research carried out during two cycles. Data collection implemented in the second semester of academic year 2016/2017. This research measure learning activity and learning outcomes. Learning activity measure with observation sheet and learning outcomes measure with written test consist of multiple-choice question as much as 20 items. Student learning activities collected during the learning process observed by 3 observers using observation sheet, then learning outcomes data obtained through evaluation when teachingâ€™s time first and second meeting was done and on third meeting was evaluation.Â This matter occurs on each cycle. All the data obtained were analyzed through three ways: qualitative analysis for student learning activities, quantitative for student learning outcomes. Results of research on student learning activity that has been analyzed shows the average in the first cycle of 55.6%, while in the second cycle of 67.2%, so the difference in the increase of 11.6%. Student learning outcomes also increased where the average value on observation data of 69.6, 64.4 the first cycle, and the second cycle 74.8. It can be concluded that the application of learning strategy Everyone is a Teacher Here can increase the activity and student learning outcomes. Keywords: everyone is a teacher here learning strategy, learning activities, learning outcomes.